Les partícules modals alemanyes i els seus equivalents en català des d’una perspectiva contrastiva - Ferrer Mora, Hang (Caplletra. Revista Internacional de Filologia, 2001)
In this paper we present a first approach to the German modal particles and their equivalents in Catalan. The German modal particles are a word group described in the German linguistics with functional criteria which does not exist in any romance language: this is also the case with Catalan. The meaning of modal particles belongs to the pragmatic level and is related to the speaker’s attitudes, but modal particles show some other discursive properties as well. Firstly, German modal particles as a linguistic phenomenon will be described. Secondly, some of their equivalents in Catalan will be established by means of comparing original literary texts in German and their translation into Catalan. Finally, all linguistic means of translation for the German modal particles in Catalan will be classified.